"You do not live in my skin": embodiment, voice, and the veteran. Issue 1 (3rd May 2016) - Bulmer, Sarah; Jackson, David
Abstract : In this paper we challenge the fundaments of academic engagement with, and representation of, veterans' embodied experiences. Drawing on work we have undertaken at a number of recent conferences to open up the format of academic discourse to a more dialogue-oriented form of engagement, we try to bring the same principles and problems into written discourse. This paper weaves between the monologic form of academic argument, and the open explorative form of the dialogue, in an attempt to question core assumptions about veteran identity. Both of us are concerned with the politics of claims to "know" the veteran experience by researchers, policymakers, and the media. The paper is an attempt to take seriously a politics of embodiment, of voice, and of listening as a way of fundamentally reorienting what we think we "know" about veteran experience and how we go about our research. Above all, this paper is an intervention. It is an attempt to go beyond using notions of "embodiment" as a heuristic device, and to operationalize this analytic in a challenge to the limits and possibilities of academic forms of representation. We argue that we need new ways of generating knowledge about embodied experience and a different understanding of what knowing means in this context. We propose "the conversation" as an alternative mode of research praxis.